2021
DOI: 10.1177/23094990211006936
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine TB – Current concepts in management

Abstract: Objective: Cervical tubercular disease (CTB) is a rare pathology and constitutes 3–5% of all spinal TB. It includes atlantoaxial TB and sub-axial TB. As the literature evidence on this subject is scarce, majority of issues concerning CTB are still controversial. The current narrative review comprehensively discusses the various aspects related to CTB. Literature search: An elaborate search was made using keywords cervical tuberculosis, atlantoaxial tuberculosis, sub-axial tuberculosis, and cervico-thoracic tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 92 publications
1
38
0
Order By: Relevance
“…Cervical tuberculosis lesions were usually located in the anterior and middle column of the vertebra. Although there were several surgical approaches (anterior, anterior combined with posterior, and endoscopy-assisted anterior), the anterior approach was still a practical method for surgery, since the simple structure of incision, convenient procedure of internal xation, su cient exposure of lesion, and less recurrence of infection [1,2]. In this cohort, all patients with cervical tuberculosis had lesions concentrated in the lower cervical spine (C3 ~ C7), 23 patients with lesions involving more than two vertebral bodies, and 12 patients with typical symptoms of spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cervical tuberculosis lesions were usually located in the anterior and middle column of the vertebra. Although there were several surgical approaches (anterior, anterior combined with posterior, and endoscopy-assisted anterior), the anterior approach was still a practical method for surgery, since the simple structure of incision, convenient procedure of internal xation, su cient exposure of lesion, and less recurrence of infection [1,2]. In this cohort, all patients with cervical tuberculosis had lesions concentrated in the lower cervical spine (C3 ~ C7), 23 patients with lesions involving more than two vertebral bodies, and 12 patients with typical symptoms of spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…The use of internal xation in the management of infectious diseases is still controversy [1,2,14]. Although previous theories had suggested that bio lms form on the surface of internal xation, which may be not conducive to the control of infection [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of neuro-deficits is also more. [ 3 ] Physicians often attribute neck pain to cervical spondylosis. We present a case of CTB, which was initially labeled as cervical spondylosis and conservatively managed.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of abscess formation, different surgical options have been analyzed over many decades and have been found to be efficacious in combination with drug treatment [3]. Tuberculous spondylitis, or Pott disease, can lead to degeneration and even caseous necrosis of intervertebral discs, as can be seen between C3/4 and C6/7 above, or lytic destruction of vertebrae, as highlighted in C5 [4]. Globalization can result in the emergence and reemergence of infectious diseases such as TB in low-incidence countries [5].…”
mentioning
confidence: 99%